Improvement of the properties of combustion by-products from grate boilers - Sobieraj , Jakub; Gądek, Waldemar; Wnorowska , Joanna; Tymoszuk , Mateusz; Kalisz , Sylwester (Instal, 2020)
The paper presents research on the improvement of the properties of post-combustion products (UPS) from grate boilers, in which these properties are changed with the help of fuel additives. In the case of research described in the article, selected fuel additive is halloysite which is an aluminosilicate mineral clay. Halloysite as a material with the structure of nanotubes has a well developed specific surface, what makes it a very good sorbent. The presented results show the influence of fuel additive on the Ash Fusion Temperatures (AFT) and the oxide composition of ash. The article also contains a proposal of optimal dose of halloysite in relation to chlorine content in fuel, as well as a general description of the model process of addition selection and reactions that need to be taken into account.
Keywords: biomass; additives; fuel additives; halloysite